Application of Real Time PCR for the Detection and Enumeration of Vibrio parahaemolyticus from Seafood in Sarawak (Malaysia) - Lesley, Maurice Bilung; Velnetti, Linang; Kasing, Apun; Samuel, Lihan; Cheah, Yoke Kqueen; Micky, Anak Vincent (UNIMAS Publisher, 2015)
Vibrio parahaemolyticus has been associated as the major cause of food poisoning and gastroenteritis in many countries including Southeast Asia. Their human infection is regularly associated with the consumption of raw or undercooked seafood and contaminated water supplies. A rapid method of detection is important to monitor the occurrence of V. parahaemolyticus in both food and environment samples especially in Malaysia. Thus, the aim of this study was to detect and enumerate V. parahaemolyticus from seafood by using the real-time PCR based on the SYBR green assay. targeting the thermolabile (tl) gene. The assay was applied on 24 seafood samples comprised of six cockles, six prawns, six squids and six fishes. In this study, all of the six cockles and prawns were positive for the presence of V. parahaemolyticus while fish samples have only two positive isolates. However, this study recorded no presence of V. parahaemolyticus in squids. Overall, the real-time PCR assay was proven to be highly specific, and is sensitive in detecting and enumerating V. parahaemolyticus in the seafood samples. In addition, this study has proven that seafood (especially cockles and prawns) are potential sources for V. parahaemolyticus